Regression Model for Socio-demographic, Behavioural and Occupational Risk Factors in Lumbar Disc Herniation (LDH) and Lumbar Disc Degeneration (LDHD)-In Comparison to Apparently Healthy Subjects - Withanage, ND; Perera, S; Peiris, H; Prathapan, S; Athiththan, LV (International journal of human and health sciences, 2021)
Objective: Present study was aimed to develop a regression model for selected sociodemographic, behavioural and occupational factors with lumbar disc herniation (LDH) and lumbar disc hearniation and degeneration (LDHD) in a selected population in comparison to healthy individuals.Materials & Methods: The study was conducted using 104 cases with disc herniation and controls (n=104) without LDH. Analysis was conducted in sub groups of patients with LDH (n=67) and LDHD (n=37) in comparison to control subjects. Pre-tested questionnaire was administered to all participants to gather information.Results & Discussion: Among the cases 35.6 % presented with LDHD while 64.4 % had only LDH. Among the socio-demographic characters, body mass index <25 kgm-2 was a significant protective factor for both LDHD (OR=0.31; 95% CI=0.13-0.72) and LDH (OR=0.39; 95% CI=0.20-0.77). Involvement in daily activities with heavy (OR=5.1; 95 % CI=2.1-11.8) and moderate strain (OR=3.1; 95 % CI=1.5-6.6) to back, sitting more than eight hours per day (OR=5.1; 95 % CI=1.0-25.7), smoking (OR=5.0; 95 % CI=1.5-16.4) and sleeping in supine position (OR=2.09; 95% CI=1.09-4.06) were significant risk factors for LDH. Only daily physical activities with heavy strain act as a significant risk factor (OR=3.1; 95 % CI=1.1-8.5) for the development of LDHD. Types of mattresses used did not have a significant difference among cases and controls. Majority of cases (56.7 %) did not know the causative factor that led to LDH. According to the regression model, BMI, smoking and involvement in physical activities with moderate and heavy strain to back were considered as significant risk factors for the development of LDH or LDHD.Conclusion: In regression model BMI, smoking and daily physical activities with moderate and heavy strain to back were found to be the significant risk factors for development of LDH or LDHD.International Journal of Human and Health Sciences Vol. 05 No. 04 October’21 Page: 424-434